Evaluación de las eficiencias de conducción en los canales de derivación de la comisión de usuarios de sausal, su impacto en la dotación de agua en la distribución - Tandaypan Rodriguez, Hipolito (2015)
The present study aims to evaluate the efficiencies of conducting channels bypass Commission Sausal User Chicama Valley , in relation to the requirement of water supply in distribution , for which the method was applied field data collection and systematization of information. In the field phase , through gauging input and output at each point of the stations were established along the canal, with the results obtained will serve to verify the requirement for the provision of appropriate water according Distribution Plan Water , as well as identify areas for expanding agricultural frontier. In the phase of systematization of field information was obtained driving efficiency in the Pampas Jagiiey channel is 78 % in the channel is 65 % Salinar Burning in the Barranca Channel Plan 2 is 85 % and channel Chicamita it is 84 %. It should be noted that the value of driving efficiency depends directly on the texture of the soil where they are located , the condition of the canals and the entire infrastructure of the irrigation system , also the extension of the agricultural frontier will depend on the water allocated according to plan cultivation and irrigation . In determining the inventory of the irrigation water infrastructure such as irrigation canals , control structures and decision shows that users incur an oversight in the maintenance of canals and irrigation infrastructure ; so it is underlined that the authorities monitor compliance with the plan to declare cultivation and irrigation users. In this respect the results of the study , it was determined that the efficiency of average driving for Users Commission Sausal is 77.85 % which is below the efficiency of driving I present the Moche Valley ( 81.50 % ) in year But this 2005.Sin regarding PROFODUA studies ( 2009 ) which considers driving efficiency on average for 75 % Chicama Valley . Compared to the average driving efficiency coated channels whose value is 95 % , the percentage obtained is below assigned